2017
DOI: 10.1121/1.5007720
|View full text |Cite
|
Sign up to set email alerts
|

Temporary hearing threshold shift in a harbor porpoise (Phocoena phocoena) after exposure to multiple airgun sounds

Abstract: In seismic surveys, reflected sounds from airguns are used under water to detect gas and oil below the sea floor. The airguns produce broadband high-amplitude impulsive sounds, which may cause temporary or permanent threshold shifts (TTS or PTS) in cetaceans. The magnitude of the threshold shifts and the hearing frequencies at which they occur depend on factors such as the received cumulative sound exposure level (SELcum), the number of exposures, and the frequency content of the sounds. To quantify TTS caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Within 3 hours of the initial exposure, TTS decreased by 2.9 dB, with full recovery to baseline estimated to occur within 12 to 55 hours. Similarly, Kastelein et al (2017a) observed onset of ~4 dB TTS in harbor porpoises after exposures to multiple airgun shots (10 to 20) with sound exposures of SELcum 188 to 191 dB re 1 µPa 2 s. Porpoise TTS recovery was observed within 12 min post exposure (Kastelein et al 2017a). Overall, these studies demonstrate that mammal TTS onset can occur from impulsive sounds, and auditory recovery to pre-exposure conditions have been observed within minutes to days.…”
Section: Seismic Airgunmentioning
confidence: 55%
See 1 more Smart Citation
“…Within 3 hours of the initial exposure, TTS decreased by 2.9 dB, with full recovery to baseline estimated to occur within 12 to 55 hours. Similarly, Kastelein et al (2017a) observed onset of ~4 dB TTS in harbor porpoises after exposures to multiple airgun shots (10 to 20) with sound exposures of SELcum 188 to 191 dB re 1 µPa 2 s. Porpoise TTS recovery was observed within 12 min post exposure (Kastelein et al 2017a). Overall, these studies demonstrate that mammal TTS onset can occur from impulsive sounds, and auditory recovery to pre-exposure conditions have been observed within minutes to days.…”
Section: Seismic Airgunmentioning
confidence: 55%
“…Both fish and marine mammals can recover from TTS, with recovery times to "baseline" occurring on the order of minutes to days (Popper et al 2005;Lucke et al 2009;Kastelein et al 2008Kastelein et al , 2012Kastelein et al , 2017a. Although PTS and TTS are useful metrics to determine auditory injury, there is uncertainty as to the environmental relevance of measurable auditory shifts to overall animal fitness and survival (Tougaard et al 2016).…”
Section: Effects On Hearingmentioning
confidence: 99%
“…While kurtosis can help describe impulsive signals, it is sensitive to variables such as the level and duration of impulses, the temporal structure of the noise, and the duration of the noise sample over which the kurtosis is calculated. Hamernik et al (2003) reported that the kurtosis stabilized for windows greater than 30 s, Lei et al (1994) calculated kurtosis over a time window of 256 s, Martin (2019) recommended calculating kurtosis over a one-minute window, Kastelein et al (2017) used a one-second time window, and Erdreich (1986) used a time window of 11 s. The duration over which to calculate kurtosis is arbitrary, which is highlighted by the varying time duration in the referenced studies. If interest is in marine mammal perception of a certain sound, the time duration could be chosen based on the physiological factors of hearing for a species of interest (Erdreich, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Playback experiments using pile driving and airgun pulses show porpoise hearing loss at low frequencies (4 and 8 kHz; Kastelein et al, 2015Kastelein et al, , 2017, although experiments with tonal sounds show TTS at increasing frequencies above the exposure frequency as signal SPL increases (Kastelein et al, 2014a). It is unclear how TTS or PTS at low frequencies will impact the ultimate fitness of harbor porpoises, but impacts on their ability to forage, navigate and communicate will likely be negligible because there is no overlap with the high-frequency content of their echolocation clicks and communication signals (115-135 kHz;Clausen et al, 2011).…”
Section: Noise-induced Threshold Shiftmentioning
confidence: 99%